Implikasi Pemenuhan Hak Anak Disabilitas terhadap Perkawinan Perspektif Hak Asasi Manusia - Agus Setiawan (Bulletin of Community Engagement, 2024)
This article analyzes the implications of fulfilling the rights of children with disabilities on marriage. Human rights legal regulations clearly stipulate that continuing offspring through legal marriage is a human right, including children with special needs or disabilities. The absence of a special treatment program has implications for children's rights, including the right to raise a household. The purpose of this article is to look at the implications of fulfilling the rights of disabled children in Rukti Sediyo Village, and to explore whether or not fulfilling the rights of disabled children in Rukti Sediyo Village is in accordance with a human rights perspective. This type of article is qualitative, analyzing in depth with the aim of revealing the fulfillment of the rights of children with disabilities. This field research was conducted in Rukti Sediyo Village, East Lampung. The primary data sources for this article are parents of children with disabilities and several related community figures. The research results found that children with disabilities in Rukti Sediyo Village have not received optimal fulfillment of their rights. This has implications for children's rights when they want to build a household, due to the lack of health care and mental development related to readiness to build a household. This condition is a violation of human rights, because fulfilling the rights of children with disabilities is the responsibility of everyone, not only the government but also parents. The recommendation of this article is that it is necessary to maximize the role of non-profit institutions or organizations operating in the social sector, under state organs (Non-Government Organizations/NGOs), for example the Foundation for the Development of Disabled Children (YPAC).